Cell seeding density is a critical determinant for copolymer scaffolds‐induced bone regeneration. Issue 11 (4th September 2015) - Yassin, Mohammed A.; Leknes, Knut N.; Pedersen, Torbjorn O.; Xing, Zhe; Sun, Yang; Lie, Stein A.; Finne‐Wistrand, Anna; Mustafa, Kamal
Abstract Constructs intended for bone tissue engineering (TE) are influenced by the initial cell seeding density. Therefore, the objective of this study was to determine the effect of bone marrow stromal stem cells (BMSCs) density loaded onto copolymer scaffolds on bone regeneration. BMSCs were harvested from rat's bone marrow and cultured in media with or without osteogenic supplements. Cells were seeded onto poly(l‐lactide‐co‐ε‐caprolactone) [poly(LLA‐co‐CL)] scaffolds at two different densities: low density (1 × 106 cells/scaffold) or high density (2 × 106 cells/scaffold) using spinner modified flasks and examined after 1 and 3 weeks. Initial attachment and spread of BMSC onto the scaffolds was recorded by scanning electron microscopy. Cell proliferation was assessed by DNA quantification and cell differentiation by quantitative real‐time reverse transcriptase‐polymerized chain reaction analysis (qRT‐PCR). Five‐millimeter rat calvarial defects (24 defects in 12 rats) were implanted with scaffolds seeded with either low or high density expanded with or without osteogenic supplements. Osteogenic supplements significantly increased cell proliferation (p < 0.001). Scaffolds seeded at high cell density exhibited higher mRNA expressions of Runx2 p = 0.001, Col1 p = 0.001, BMP2 p < 0.001, BSP p < 0.001, and OC p = 0.013. More bone was formed in response to high cell seeding density (p = 0.023) and high seeding density with osteogenic medium (p = 0.038). Poly (LLA‐co‐CL) scaffolds could be appropriate candidates for bone TE. The optimal number of cells to be loaded onto scaffolds is critical for promoting Extracellular matrix synthesis and bone formation. Cell seeding density and osteogenic supplements may have a synergistic effect on the induction of new bone. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3649–3658, 2015.